ENHANCING SOCIAL SECURITY AMID ARMED CONFLICT: TOWARD LEGAL PROTECTIONS FOR WORKERS FACING EMPLOYMENT LOSS - Amriyati, Amriyati; Nurbaiti, Siti; Permanasari, Arlina; Artha, Willy (Universitas Syiah Kuala, 2024)
The significant impact of armed conflict on social conditions can be mitigated through the establishment of certain preventive measures to protect social security in cases of employment loss resulting from armed conflict. This study focuses on the social conditions arising from armed conflict and the national laws pertaining to worker social security in cases of employment loss, with a specific focus on Ukraine, Israel, Palestine, and Libya. Utilizing a doctrinal and socio-legal methodology, this article aims to provide insights for the development of preventive legal protections for workers facing employment loss in the aftermath of armed conflicts. The study reveals that social conditions are disrupted, leading to many workers losing their jobs without clear access to employment loss benefits due to the lack of legal certainty within national laws during armed conflict situations. Prior to the occurrence of armed conflict, national employment laws should clearly outline the conditions under which benefits can be accessed and how these benefits can be provided to affected workers, either within the conflict zone or in neighboring unaffected countries through institutional cooperation.